A Polymorphism in the Coding Region of Il12b promotes IL-12p70 and IL-23 Heterodimer Formation - Zwiers, Antonie (2011)
Interleukin (IL)-12 and IL-23 are heterodimeric cytokines involved in the induction of Th1 and Th17 immune responses. Previous work indicated that a region on chromosome 11 encoding the IL-12 p40 subunit regulates strain differences in susceptibility to murine trinitrobenzene sulfonic acid (TNBS)-induced colitis. In addition, this region determines strain differences in LPS induced IL-12 responses. Here we investigated how polymorphisms in the coding region of murine Il12b influence IL-12 and IL-23 heterodimer formation. Transfection studies using constructs containing IL-12p35 linked to either IL-12p40 from the colitis-resistant C57Bl/6 strain or to the polymorphic p40 variant from the colitis-susceptible SJL/J strain demonstrated that SJL/J-derived p40 constructs synthesized significantly more IL-12p70 than constructs harboring the C57Bl/6-p40 variant. This could not be attributed to differences in synthesis rate or secretion implicating a higher affinity of SJL/J derived IL-12p40 for its IL-12p35 subunit. This higher affinity is also associated with increased IL-23 synthesis. In addition, C57Bl/6 mice transgenic for the SJL/J 40 variant synthesized significantly more IL-12p70 and were more prone to develop colonic inflammation than did C57Bl/6 mice transgenic for the C57Bl/6-p40 variant upon LPS challenge. The more efficient binding of the polymorphic Il12b variant to p35 and p19 is most likely due to conformational changes following differential glycosylation as a consequence of the polymorphism. The high synthesis rate of the mature cytokines resulting from this efficient binding can lead to rapid pro-inflammatory skewing of immune responses and distortion of the homeostatic balance underlying the higher susceptibility for colitis.